2013
DOI: 10.1021/ef401788m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biomass Chemical Properties on Torrefaction Characteristics

Abstract: Different biomass types may differ with respect to torrefaction characteristics, and an improved understanding and ability to predict the torrefaction performance is, therefore, desired. In this study, the influence of the chemical properties (lignocellulose composition and alkali content) on the torrefaction behavior with respect to mass loss and grindability is investigated by simultaneous thermal analysis (STA) and by using a combined torrefaction and grinding reactor. The torrefaction behavior of six raw b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 23 publications
3
52
0
Order By: Relevance
“…The demineralization of wheat straw decreases the required holding time for complete pyrolysis from 2 to 1 s at 1000 ∘ C. The leached wheat straw of size N 0.425 mm obtained a higher char yield at 600 ∘ C than untreated straw within 1 s. The present results show that at lower temperatures a high alkali content induces lower char yield, similarly to results of Saleh et al [2]. Moreover, the holding time effect on the weight loss is not particularly dependent on the straw particle size.…”
Section: Effect Of Holding Timesupporting
confidence: 89%
See 1 more Smart Citation
“…The demineralization of wheat straw decreases the required holding time for complete pyrolysis from 2 to 1 s at 1000 ∘ C. The leached wheat straw of size N 0.425 mm obtained a higher char yield at 600 ∘ C than untreated straw within 1 s. The present results show that at lower temperatures a high alkali content induces lower char yield, similarly to results of Saleh et al [2]. Moreover, the holding time effect on the weight loss is not particularly dependent on the straw particle size.…”
Section: Effect Of Holding Timesupporting
confidence: 89%
“…Fine biomass milling is energy-consuming, and fibrous particles with low bulk densities may cause feeding problems. Large biomass particles may create challenges with flame stability, burnout and ignition [1,2]. The challenge of achieving high fuel conversion at short residence times depends on biomass origin, morphological changes of fuel particle of different sizes, char yield, fuel reactivity, heating rate, local oxygen concentration and temperature in the boiler [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers (Saddawi et al, 2012;Saleh et al, 2013) have reported that potassium had the effect on reducing the degradation temperature and promoting volatile release during the process of torrefaction. Although the mass yield of W-RH during the process of torrefaction pretreatment was significantly higher than that of RH, the higher heating values between them had no obvious difference.…”
Section: Influence Of Pretreatment On Fuel Characteristicsmentioning
confidence: 99%
“…Thus, CO 2 released with biofuels can be reconsumed faster by plants via photosynthesis than the time needed to regenerate coal. The milling process is a necessary step in suspension firing [1]. Size reduction improves fuel conversion processes because of the creation of larger reactive surface areas [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of particle models depends on both correct size distribution and characterization of fuel inhomogeneity in terms of shape and structure. The objective of this study is twofold: (1) to provide a geometrical description of biomass particles that can be used in combustion model; (2) to make suggestions for the size and shape of biomass particles. In this work, the biomass particles' size and shape are characterized by using both 2D dynamic imaging analysis and microscopy.…”
Section: Introductionmentioning
confidence: 99%